WORK MEASUREMENT IN HRM: AN EVALUATION TOOL FOR DETERMINING EMPLOYEE TIME AND WORKLOAD STANDARDS - Nazwar Muhajir Saimima; Ramlawati; Nur Alam (Journal Informatic, Education and Management (JIEM), 2026)
Work measurement plays a crucial role in Human Resource Management (HRM) as an objective instrument for determining employee time and workload standards. In practice, the lack of accurate work measurement often leads to unrealistic performance targets and workload imbalances, which negatively impact employee performance and productivity. This article aims to analyze the role of work measurement as an evaluation tool in determining time and workload standards in the HRM context. The research method used is a literature study with a descriptive-analytical approach through a review of relevant scientific journals, books, and academic publications. The results of the study indicate that work measurement contributes significantly to establishing objective and realistic time standards, supporting proportional workload distribution, and indirectly improving employee performance and productivity by creating ergonomic and psychologically conducive working conditions. This study concludes that work measurement is a strategic HRM instrument that supports data-based decision-making and sustainable performance management.